Design of Android Based on Android Based Learning and Introduction to Muslim Cendiciawan Applications - Dimas Ari Sanjaya; Yulia Darnita (Penerbit Jurnal Indonesia, 2022)
Along with the development of information technology, nowadays many devices have been created to make it easier to access information. The information system about Muslim scholars is currently still dominated by books. Therefore, a learning application will be made that utilizes information technology based on mobile android. The purpose of this research is to produce applications that are easy to understand in understanding the influence of Muslim scholars in the development of science and provide information to children about Muslim alcoholism in influencing the development of science. The research method used in this study uses the Waterfal method. The results that can be accessed from this study is an android application that contains information on intellectual biographies. Based on the results of the test data on the design of learning applications and the introduction of android-based Muslim scholars using questionnaire testing to the teacher council. It is found that this application is included in the